PENGARUH KONFORMITAS TERHADAP PERILAKU MEROKOK PESERTA DIDIK KELAS X DAN XI DI SMA NEGERI 1 RANAH BATAHAN - Anggina Putri Nst; Yasrial Chandra; Joni Adison (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the phenomenon of students who start smoking due to peer influence, the tendency to follow group habits, and minimal awareness of the dangers of smoking. The purpose of this study is to describe: (1) the level of student conformity, (2) student smoking behavior, and (3) the influence of conformity on smoking behavior in grades X and XI students at SMA Negeri 1 Ranah Batahan. The study used a quantitative approach with a simple linear regression analysis method. The sample consisted of 115 respondents from a total population of 161 students selected through proportional random sampling techniques. The results showed that conformity and smoking behavior were in the fairly high category. It is known that conformity influences smoking behavior by 28%. This study suggests that guidance and counseling teachers and school principals provide intensive education and guidance to reduce the negative influence of conformity on smoking behavior.